The Impact of Workplace Facilities and the Role of Work Discipline in Enhancing Employee Performance - Siti Rochanah; Hardin; Fitri Rahmawati (www.amertainstitute.com, 2025)
This investigation endeavors to analyze The Impact of Workplace Facilities and the Role of Work Discipline in Enhancing Employee Performance at Dinas Ketahanan Pangan dan Pertanian Kabupaten Purworejo. Job Performance of Employees is a vital component in achieving organizational, therefore it is important to pay attention to aspects that can enhance work effectiveness. Adequate work facilities and high work discipline are believed to contribute positively to employee effectiveness. This study employs a quantitative methodology using a survey technique. Information was gathered via questionnaires handed out to 70 staff members Dinas Ketahanan Pangan dan Pertanian Kabupaten Purworejo. Analysis of the data was carried out through multiple linear regression methods to test the influence of two independent variable, namely workplace facilities and Work discipline in relation to employee performance, the dependent variable in this study. The findings indicate that workplace facilities positively and significantly influence employee performance. This means that the better the work facilities provided, the higher the employee performance. Additionally, work discipline also has a proven positive and significant effect on employee performance. Employees with high discipline tend to exhibit better performance. The results suggest that enhancing workplace amenities and reinforcing work discipline serve as effective approaches to boost employee performance at Dinas Ketahanan Pangan dan Pertanian Kabupaten Purworejo. This study recommends that the organizational management continuously improve the quality of work facilities and implement policies that support work discipline to achieve optimal performance.